TESTİNG AND ANALYZİNG THE PRİCE BUBBLES İN TURKİSH EDAM (Third Sector Social Economic Review, 2022)
Asset prices exhibit tremendous boost and bust periods, that are often not justified by economic fundamentals. This explosive behavior in asset price series may imply bubbles. Bubbles create erratic price spike periods. These periods of high price volatility are possible to observe in day-ahead electricity markets (EDAMs). The extreme price fluctuations in electricity prices can be considered as deviations from the fundamental values or bubbles. High electricity prices can significantly affect the consumer behavior to make consumers opt for other energy sources that are cheaper. They also have an important impact on key macroeconomic variables such as consumer price index and economic growth. In this paper, we test and analyze the existence of price bubbles in Turkish EDAM by applying the right-tailed ADF unit root tests: RADF, SADF, and GSADF tests, using monthly supply-adjusted prices between December 2011 and April 2021. Empirical results reveal two bubble periods in 2015 and 2018.
Keywords: Rational Bubbles; bubbles in electricity prices; Right-tailed ADF tests; RADF test; SADF test; GSADF test.